Increasing Understanding of Medicines in the Community Through the Implementation of DAGUSIBU as a Prevention of Antibiotic Resistance in Pasir Jengkol Village, Karawang Regency - Zahra, Aliya Azkia; Malau, Jekmal; Kasasiah, Ahsanal; Ratnasari, Devi; Septiani, Dia; Sholih, Mally Ghinan (Universitas Malahayati Lampung, 2025)
ABSTRACT Antibiotic resistance occurs when microorganisms become unresponsive to antibiotic treatment, rendering common therapies ineffective against infections. As a result, the infection becomes increasingly challenging to treat, posing a heightened risk of severe disease progression and increasing the risk of spreading the disease. The causes of the emergence of antibiotic resistance include a number of factors, including excessive use of antibiotics from self-medication, to inappropriate disposal of antibiotic drugs. Karawang Regency, a region in West Java which consists of 10 sub-districts and has a population of more than 2.4 million people. Research conducted in Karawang shows the potential for antibiotic resistance based on use and the environment. It is known that the people of Karawang Regency have poor knowledge and perception regarding antibiotic resistance and use, one of which is Pasir Jengkol village. Therefore, it is necessary to increase understanding of medicines among the people of Karawang Regency, including by socializing the DAGUSIBU movement (Dapatkan, Gunakan, Simpan dan Buang Obat) or Proper Use, Storage and Disposal of Medications and its implementation as a measure to prevent antibiotic resistance. The output of this activity is primarily an increase in understanding of public knowledge through questionnaires which are analyzed using statistics. The results obtained were then tested using a statistical test showing a significant influence (Sig 0.002) increase in knowledge through the difference in pre-test and post-test scores. This outreach activity, which provides educational materials on preventing resistance, has positively impacted the Pasir Jengkol community's knowledge. Therefore, this socialization initiative can be replicated in other areas, particularly in Karawang Regency. Keywords: Antibiotic, Drug Resistance, DAGUSIBU, Karawang.